Inter-regional mobility in the accession countries: a comparison with EU15 member states - Peter Huber (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
This paper uses a data set covering 9 EU15 member states and 7 candidate countries and new member states to compare inter-regional migration patterns in the 1990s. We find that the level of migration is lower in candidate countries and new member states than in EU15 member states. Also in contrast to the EU15 member states, migration has fallen in candidate countries and new member states. This casts doubt an the viability of migration as an adjustment mechanism. Estimating place-to-place models of migration we find that migration is less reactive to regional disparities in candidate countries and new member states than it is in EU15 member states. If reaction to labor market disparities were similar to EU15 states, net migration should increase by a factor of between 2 and over 10.
Keywords: 330; regionale Mobilität - internationaler Vergleich; Binnenwanderung; regionaler Arbeitsmarkt; regionale Disparität; Mobilitätsbereitschaft - Determinanten; demografische Faktoren; ökonomische Faktoren; Arbeitsmarktgleichgewicht; Arbeitskräftemobilität; Migration - Modell; Europäische Union; Osteuropa